Persistence of Resistance Alleles 1781, 2041, and 2078 in the Absence of Herbicide Selection. (1st September 2017) - Saini, Rupinder Kaur; Malone, Jenna; Preston, Christopher; Gill, Gurjeet
Abstract : Core Ideas: This research investigated whether a fitness penalty exists for three known mutations (Leu‐1781, Asn‐2041, and Gly‐2078) in clethodim‐resistant rigid ryegrass populations under wheat competition. The results revealed that in the absence of herbicide selection, no fitness cost was associated with Leu‐1781 and Asn‐2041 alleles, but Gly‐2078 alleles increased in frequency. The absence of fitness penalties associated with these resistant alleles suggests their frequency will not decrease over time in the absence of clethodim use. In Australia, over‐reliance on clethodim has resulted in the evolution of clethodim resistance in rigid ryegrass ( Lolium rigidum Gaudin) populations. Many of these resistant populations contain amino acid modifications in acetyl co‐enzyme A carboxylase (ACCase), the target‐site for this herbicide. This study was conducted to determine whether a fitness penalty exists for three known mutations (Leu‐1781, Asn‐2041, and Gly‐2078) in clethodim‐resistant populations in the absence of herbicide selection pressure and presence of crop competition. In 2014, F2 seedlings of three clethodim‐resistant rigid ryegrass populations were planted in wheat ( Triticum aestivum L.) crop under two densities (100 and 200 plants m −2 ). Sequencing of all individuals of each rigid ryegrass population was done to establish the initial frequency of each allele (no mutation, Leu‐1781, Asn‐2041, and Gly‐2078). The F2 plants were allowed to set seed and seeds were collected at the end of the season. In 2015, seedlings established from seed collected in 2014 were grown, and the sequence of ACCase gene examined to determine the change in frequency of each resistant allele. The results showed that there was no significant change in the frequency of Leu‐1781, and Asn‐2041 alleles in rigid ryegrass populations over one generation in the absence of clethodim use. However, Gly‐2078 increase was identified in three populations, even under different competition levels. The absence of fitness penalties associated with these resistant alleles suggests that their frequency will not decrease over time in the absence of clethodim use.